JUSTICE IN GOVERNMENT POLICIES WITHIN THE FRAMEWORK OF PANCASILA - Jamal , Ode; Hadi, Ade Sopyan (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
The problem of inequality in Indonesia remains a growing issue. With a population of over 270 million, inequality remains an unresolved challenge. This study aims to further explore the concept of Justice in Government Policy within the Pancasila Framework. The research method used in this study is a qualitative approach, while the type of research used is a literature study. The results of this study indicate that the principle of justice within the context of Pancasila has been implemented by various government agencies such as the Ministry of Education and Culture, the Ministry of Religious Affairs, the Ministry of Transportation, Gadjah Mada University, and the BPJS Kesehatan (Social Security Agency for Health). This principle of justice is implemented through attention to disabilities, the principle of mutual cooperation within BPJS Kesehatan, and the existence of affirmative action programs to obtain educational scholarships for people living in the outermost, outermost, and remote areas. The conclusion of this study is that the principle of justice within the context of Pancasila has been implemented.